Physicochemical Properties of Sponge Cake Fortified by Olive Stone Powder - Raziyeh Jahanbakhshi; Sara Ansari (Journal of Food Quality)
Olive stones are by-products in olive oil extraction and in table olive industries. Nonetheless, they contain beneficial nutritive elements such as fiber, phenolic compounds, and omega-3 and -6 fatty acids. In this research, olive stone powder (OSP) was used to substitute 0, 15, 25, and 35% of wheat flour in sponge cake recipe. The effects of this substitution were examined on the physiochemical and sensory properties of sponge cakes. The fiber content and the total phenolic compounds of the cake samples increased significantly from 0.67 to 8.60% and from 89.14 to 739.23 μg/ml, respectively, by increasing the OSP from 0 to 35%. With increased amounts of OSP, batter viscosity and consistency decreased (from 27430 to 11030 centipoise and from 8.67 to 13.42 g/s, respectively), while the specific volume of the cakes increased (from 2.08 to 6.21 cm3/g). Parallel to the increased levels of substitution, the hardness and springiness of cakes decreased, whereas the gumminess and chewiness increased. The crumb structure of OSP-enriched cakes was more porous than that of the control. Color analysis indicated significant differences between the control and treated samples regarding L∗a∗, and b∗ parameters. Cakes had colors that were darker than expected when treated with OSP (p<0.05). According to sensory evaluations, no significant differences were observed between OSP cakes and the control sample in terms of taste, after taste, color, and odor (p>0.05). In conclusion, substituting OSP for flour by 25% can yield acceptable dietary fiber content and antioxidant phenolic compounds while showing no undesirable changes in sensory properties.